(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To examine the role of relatives in supporting Nurses in the care of inpatient and to explore their challenges faced in the care of inpatient Subject and method: Research design: Cross-sectional descriptive study. Research population: Nurses, inpatients, and relatives of patients in the internal medicine, surgery, and emergency departments of Nguyen Trai Hospital during the study period. Results: Relatives of patients engage in inpatient care in an active and efficient manner. Relatives in the surgery and internal medicine departments provided substantial support in caring for inpatients. There are 29/69 criteria for receiving support from relatives, the majority of which are basic care criteria: assistance with daily activities, rest, and body hygiene; care for pressure ulcers; patient fall prevention methods; pain management and safety techniques; support in regulating the environment and eating. Problems sharing treatment information with nurses are the most challenging part of care for inpatients. Relatives expressed the need for information related to the patient’s progress, treatment plan, and nursing care plan. Conclusion: Relatives play an active role in supporting inpatients with daily activities. The results can serve as a foundation for the hospital to develop policies and health education programs aimed at enhancing the effectiveness of relatives’ support in inpatient care.